Radiation sources in the environment near NPP Temelin - Thinova, Lenka; Matolin, Milan; Ploc, Ondrej; Cechak, Tomas (Applied radiation and isotopes, 2010)
A widely discussed question is how much a nuclear power plant really contributes to irradiation of the people living in its vicinity. A number of laboratory and in situ measurements were performed in the area surrounding NPP Temelin, on the basis of which we can specify the irradiation of this area from various sources. The evaluation includes the contributions from natural sources, such as radon, terrestrial radiation and cosmic radiation, together with the contribution from inhalation and ingestion of radionuclides. Medical irradiation and nuclear fallout are also included.
Keywords: radiační pozadí; obsah radioaktivních látek v organizmu; jaderné elektrárny; Environmental Exposure; vystavení vlivu životního prostředí; Body Burden; Radiation Monitoring; Humans; Česká republika; lidé; Background Radiation; monitorování radiace; Czech Republic; Nuclear Power Plants